Analysis of reproductive hormones and morphometric attributes in Thamankaduwa White male cattle - Siriwardana Tharinda Dhilshan De Silva; Oshan Bimsara Gunawardena; Mylvaganam Pagthinathan; Pradeepa Silva; Indunil Pathirana (Cluj Veterinary Journal, 2023)
Despite a few attempts in exploring genetic variability, management systems, and morphometric descriptions, Thamankaduwa White cattle in Sri Lanka has not been subjected to any evaluation of their endocrinological distinctiveness, especially related to reproduction. The main aims of the present study were to: (1) investigate the dynamics of circulating insulin-like peptide 3 (INSL3) and testosterone in Thamankaduwa bulls during development, and (2) assess the association among INSL3, testosterone and selected morphometric parameters, namely, body weight, height at withers, body length, chest girth of Thamankaduwa White cattle in Sri Lanka. The blood samples were collected from male animals (n = 41) under three age categories; 3-6 months (Group Ⅰ; n = 12), 6-12 months (Group Ⅱ; n = 14) and > 12 months (Group Ⅲ; n = 15), along with their morphometric measurements. Serum INSL3 and extracted testosterone concentrations were measured by using a competitive ELISA. The detection ranges of INSL3 and testosterone assay were 0.078-80 ng/mL and 0.04-40 ng/mL, respectively. Intra- and inter-assay coefficient of variations of INSL3 and testosterone assays were 6.9% (n = 6) and 16.4% (n = 6), and 12.5% (n = 3) and 11.9% (n = 4), respectively. Serum INSL3 and testosterone concentrations ranged between 1.44 - 19.85 ng/mL, and 0.003 ng/mL - 2.81 ng/mL, respectively. The mean serum INSL3 concentrations did not differ between Gr. Ⅰ and Ⅱ (p > 0.05) but were significantly high (p < 0.05) in Gr. Ⅲ. There was a significant association (R2 = 0. 65; p < 0.05) between serum INSL3 and testosterone concentrations in Thmankaduwa White males. No strong associations were observed among hormones and the morphometric parameters tested. In conclusion, the dynamics of INSL3 and testosterone concentrations were compatible and correlated with each other in Thamankaduwa White male cattle.